2004
DOI: 10.2175/193864704784138818
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental Methanol Optimization for Enhanced Performance and Kinetics in a Step-Feed BNR Reactor

Abstract: New York City Department of Environmental Protection and Metcalf & Eddy are researching effects of supplemental carbon on step-feed biological nutrient removal reactors with respects to improve total nitrogen removals. Based on historically low methanol kinetics (0.04 -0.08 mg N/mg VSS/d) as compared to literature cited methanol kinetic rates (0.08 -0.10 mg N/mg VSS/d) and rates observed with acetate (0.12 -0.25 mg N/mg VSS/d) and considering the significantly lower costs of methanol, further investigations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…New York City, in its first full scale trials of nitrogen removal, showed a serious foam accumulation problem behind the newly introduced baffles; waste activated sludge transmitted to the digesters caused a digester cover failure at one plant ( Figure 11). The problem occurred early enough in their nitrogen removal program that they could dedicate years of pilot and plant scale research in the identification of successful foam control methods (Carrio et al, 2000, Chandran et al, 2003, Minassian et al, 2004, Pape et al, 2004, Rubino et al, 2010. Formation of nuisance foams has also been a problem in Australian step feed nitrogen removal plants (Yerrell et al, 2003).…”
Section: High Purity Oxygen Activated Sludge (Hpoas)mentioning
confidence: 99%
“…New York City, in its first full scale trials of nitrogen removal, showed a serious foam accumulation problem behind the newly introduced baffles; waste activated sludge transmitted to the digesters caused a digester cover failure at one plant ( Figure 11). The problem occurred early enough in their nitrogen removal program that they could dedicate years of pilot and plant scale research in the identification of successful foam control methods (Carrio et al, 2000, Chandran et al, 2003, Minassian et al, 2004, Pape et al, 2004, Rubino et al, 2010. Formation of nuisance foams has also been a problem in Australian step feed nitrogen removal plants (Yerrell et al, 2003).…”
Section: High Purity Oxygen Activated Sludge (Hpoas)mentioning
confidence: 99%